2017
DOI: 10.1007/s13224-017-0993-4
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and Serum Antioxidants in Women with Preeclampsia with or Without Periodontal Disease

Abstract: The results of our study show that periodontal disease may be potential risk factor for severity, progression, and even initiation of preeclampsia because of reduced antioxidant capacity or increased oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Furthermore, some studies have shown that periodontal disease may Table 3. Distribution of case and control groups according to the presence or absence of periodontal disease, categorized by the pregnancy-induced hypertension status be a potential risk factor for the initiation and development of preeclampsia because of the reduced antioxidant capacity and increased oxidative stress or free radicals [27,28]; therefore, we hypothesized that periodontitis during pregnancy was associated with preeclampsia. Several studies have reported the relationship between periodontitis and preeclampsia [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have shown that periodontal disease may Table 3. Distribution of case and control groups according to the presence or absence of periodontal disease, categorized by the pregnancy-induced hypertension status be a potential risk factor for the initiation and development of preeclampsia because of the reduced antioxidant capacity and increased oxidative stress or free radicals [27,28]; therefore, we hypothesized that periodontitis during pregnancy was associated with preeclampsia. Several studies have reported the relationship between periodontitis and preeclampsia [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…It is supported that periodontal diseases are related with adverse pregnancy effects [54]. One of the possible mechanisms underlying this interaction stated that there may be oxidative stress-related inflammation pathways in case of pregnancy and periodontal disease [5,27]. Oxidative stress is a principal supporting factor in the pathogenesis of preeclampsia and periodontal disease [27].…”
Section: Pregnancymentioning
confidence: 99%
“…One of the possible mechanisms underlying this interaction stated that there may be oxidative stress-related inflammation pathways in case of pregnancy and periodontal disease [5,27]. Oxidative stress is a principal supporting factor in the pathogenesis of preeclampsia and periodontal disease [27]. Çanakçı et al [40] evaluated the GSH-Px levels in serum, saliva, and GCF in preeclamptic and normotensive pregnant women with and without periodontal disease.…”
Section: Pregnancymentioning
confidence: 99%
See 2 more Smart Citations